The effect of the problem-based learning model and audiovisual media that based on south sumatera's local superiority to learning outcomes - Septi Handayani; Nur Ahyani; Dessy Wardiah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This research aimed at finding out the effect of the problem-based learning model and audiovisual media that based on South Sumatera's local superiority to learning outcomes. This research was using Quasi Experimental Design as the method with design Nonequivalent Control Group Design. The subjects were 45 students in Experimental Group and 45 students in Control Group. The researcher used the data collection tool in the form of pretest-posttest, observation and documentation. The average score of pretest in experimental group was 83 and average score of pretest control group was 66,8. The data of pretest and posttest in experimental group was distributed normal with the value km -0,71 and 0,80. The hypotheses was calculated by using t-test which is polled varians and and the result of t obtain was 8,598 in 0,05 significant level and the t-table is 1,987. Since the significant level showed tobtain>ttable, therefore Ho was rejected and Ha was accepted. The result of this research proved that the problem-based learning model and audiovisual media that based on South Sumatera's local superiority to learning outcomes.